Professional board examination for teachers - Busto, Arellano V. (Sampaloc, Manila : A.V.B Printing Press, 1999)
A Reviewer's main purpose should be to afford a retrospective view of materials previously studied in order that recall of such materials may be facilitated, thus enabling the examinee to answer satisfactorily the various questions presented during the examination regarding past accumulated knowledge.
Part I. General education -- Part II. Professional Education -- Part III. General Review -- Part IV. Fisheries administrative order.
Keywords: EDUCATION -- LICENSURE EXAM